A 26-Year-Old Retained Demised Abdominal Pregnancy Presenting with Umbilical Fistula - Nnadi Daniel; Bello Bashir; Ango Ibrahim; Singh Swati (Case Reports in Obstetrics and Gynecology)
This is a report on a 72-year-old postmenopausal woman who presented with passage of fetal bones through an umbilical fistula. She was diagnosed as a case of demised abdominal pregnancy, which had been retained for 26 years. She subsequently had exploratory laparotomy, evacuation of the abdominal pregnancy, hysterectomy, and bowel resection. The patient’s condition remained unstable throughout the postoperative period and she died from septicemia on the eleventh day.